Effects of the hydrogen potential and fungicide treatment on Pitaya seed germination - Thiago Alberto Ortiz; Aline Moritz; Mariana Alves de Oliveira; Lúcia Sadayo Assari Takahashi (Acta Scientiarum. Agronomy, 2014)
The objective of the present study was to evaluate pitaya seed germination under different hydrogen potentials, with or without fungicide treatment. A completely randomized design was employed under a 3 x 13 x 2 factorial scheme, corresponding to three pitaya species (white pitaya, pitaya hybrid I, pitaya hybrid II), thirteen hydrogen potentials (3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, and 9.0) and two fungicide conditions (presence and absence), with four replications. The percentage of germination, germination speed index and mean germination time were evaluated. The data were subjected to ANOVA, and the means were compared using the Scott-Knott test (p < 0.05). The pH influenced the germination speed index in white pitaya. The mean germination time was affected by the pH levels for white pitaya and pitaya hybrid II. The fungicide did not increase the germination percentage in the evaluated species.